2017
DOI: 10.1186/s12950-017-0173-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 24 h–delayed normo- and hyperbaric oxygenation in severe sepsis induced by cecal ligation and puncture in rats

Abstract: BackgroundSeptic shock remains a leading cause of death worldwide. Hyperbaric oxygen treatment (HBO2) has been shown to alter the inflammatory response during sepsis and to reduce mortality. A therapeutic window of HBO2 treatment has been demonstrated experimentally, but optimal timing remains uncertain. We investigated the effects of 24 h delayed normobaric oxygen (NBO2) and HBO2 treatment on the endogenous production of the inflammatory markers interleukin (IL)-6, tumor necrosis factor (TNF)-α and IL-10, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…HBO 2 treatment induces several immunomodulatory effects that may well explain the observed cytokine fluctuations before and after HBO 2 treatment. Studies of experimental sepsis have indicated that HBO 2 treatment exerts its antimicrobial effect by enhancement of IL‐10, which lowers IL‐6 and thereby reduces the overall mortality in HBO 2 ‐treated animals (Bærnthsen et al, 2017; Buras et al, 2006). However, we were unable to detect any fluctuations of IL‐10 after HBO 2 treatment, but this discrepancy may well be explained by our time of blood sampling immediately after treatment which does not respect the less rapid kinetics of IL‐10 (Khatri & Caligiuri, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HBO 2 treatment induces several immunomodulatory effects that may well explain the observed cytokine fluctuations before and after HBO 2 treatment. Studies of experimental sepsis have indicated that HBO 2 treatment exerts its antimicrobial effect by enhancement of IL‐10, which lowers IL‐6 and thereby reduces the overall mortality in HBO 2 ‐treated animals (Bærnthsen et al, 2017; Buras et al, 2006). However, we were unable to detect any fluctuations of IL‐10 after HBO 2 treatment, but this discrepancy may well be explained by our time of blood sampling immediately after treatment which does not respect the less rapid kinetics of IL‐10 (Khatri & Caligiuri, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β, a powerful proinflammatory cytokine primarily created by activated macrophages and monocytes, acts on a variety of immune cells including the endothelium, amplifying the inflammatory process by release of proinflammatory cytokines-such as IL-6-and reactive oxygen and nitrogen species (Schulte et al, 2013). In this context, it may be of importance to note, that both ICAM-1 and IL-6 are modified by HBO 2 treatment in experimental sepsis (Baernthsen et al, 2017;Buras et al, ,2000Buras et al, , , 2006Halbach et al, 2019). Some evidence indicates that G-CSF-a hematopoietic-cell growth factor-is involved in sepsis pathogenesis and has crucial functions on mature myeloid cells and the innate immune system during inflammation (Hamilton, 2008;Roberts & Roberts, 2005).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Studies regarding HBO as adjuvant therapy in sepsis have also been performed in the past, and its beneficial effects have been reported [12,32]. The role of cellular oxidative damage in multiple organ dysfunction syndrome is well-known.…”
Section: Discussionmentioning
confidence: 99%